Comparative Analysis of Blood Serum Minerals in NARI Suwarna Lambs on Various Feeding Plans - Pawan Chaudhary, Diksha Nautiyal, R Kavitha (Revista Electronica de Veterinaria, 2024)
The NARI Suwarna lambs are highly valued for their exceptional protein content and immediate development, thereby emphasizing the essential need of meeting their precise nutritional needs for prosperous farming. Proper nutrition performs a crucial role in determining the growth, conception and general wellness of these organisms. The observations can be influenced by external factors including climate and environment, which can impact their generalization. The goal of this investigation is to examine the mineral composition of the blood Serum in NARI Suwarna sheep that were challenged to two distinct feeding methods. A total of fifty-four mature NARI Suwarna ewes, all of identical ages, were allocated into two categories. Category I (n=27) received a regular sheep feed, whereas Category II (n=27) were permitted to graze in the pasture. The average serum quantities of Glucose (G), Phosphorus (P), Iron (Fe), Copper (Cu), Calcium (Ca) and Zinc (Zn),in lambs that were provided scientifically as well as grazed on pastures, were (10.46±0.7)mg/dl, (11.32±0.4 7.04±0.39) mg/dl, (72.43±2.69) and (7.39±0.39, 63.2±2.79) mg/dl, (1.9±0.18) ppm, (1.9±0.17, 2.15±0.22) ppm (2.12±0.19) (2.57±0.24) ppm and (2.74±0.25) correspondingly. Initial findings reveal substantial disparities in the levels of minerals present in the blood of NARI Suwarna lambs that were exposed to distinct feeding regimens. Ewes sustained under experimental feeding had elevated blood calcium and glucose contents in comparison to those kept under grassland feeding.